1998
DOI: 10.1002/(sici)1096-8628(19981228)80:5<518::aid-ajmg16>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Anencephaly-associated aganglionosis

Abstract: Autopsies of 12 consecutively born infants with anencephaly showed varying degrees of aganglionosis and lateralization defects in four of them. This seemingly regular occurrence of these three defects together suggests that they are caused by an aberration of blastogenesis that results in a polytopic field defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A number of reports include the cosegregation of HSCR with mental retardation and various dysmorphic features which include absence of the corpus callosum (isolated or in association with the Goldberg-Shprintzen [50] and Mowat-Wilson syndromes [51]). Anencephaly appears to be commonly associated and autopsies on 12 consecutive anencephalic newborns showed some degree of aganglionosis in all [52]. Dandy-Walker abnormalities are possibly associated with chromosome 9 variations [53] in a site associated with HSCR [53].…”
Section: Intestinal Atresiamentioning
confidence: 91%
“…A number of reports include the cosegregation of HSCR with mental retardation and various dysmorphic features which include absence of the corpus callosum (isolated or in association with the Goldberg-Shprintzen [50] and Mowat-Wilson syndromes [51]). Anencephaly appears to be commonly associated and autopsies on 12 consecutive anencephalic newborns showed some degree of aganglionosis in all [52]. Dandy-Walker abnormalities are possibly associated with chromosome 9 variations [53] in a site associated with HSCR [53].…”
Section: Intestinal Atresiamentioning
confidence: 91%
“…Although diffi cult to quantify, anencephaly also appears to be not infrequently associated with intestinal aganglionosis. In one reported study, autopsies performed on 12 consecutive anencephalic newborns all showed some degree of aganglionosis (32) . In addition, Dandy-Walker abnormalities are possibly associated with chromosome 9 variations (33) , a site previously associated with HSCR (34) .…”
Section: Discussionmentioning
confidence: 99%
“…GOSHS presents various common characteristics with the Mowat-Wilson syndrome (MIM 235730), which will be discussed below in section 5. HSCR has also been connected with malformations of the nervous system: defects in the neural tube closure such as anencephaly (Mathew, 1998) and meningomyelocele (Merkler et al, 1985), as well as anomalies in neuronal migration and or cerebral dysgenesis (Cass, 1990), predominantly agenesis of corpus callosum (Sayed & Al-Alaigan, 1996). These phenomena have been regarded as alterations in the embryonic development of the anterior portion of the NC (Currie et al, 1986;Hurst et al, 1986).…”
Section: Hirschsprung Disease (Hscr) or Aganglionic Megacolon And Itsmentioning
confidence: 99%